Proposed interior design scheme of Labu Sayong Centre for Jabatan Pelancongan Dan Pengindahan Bandar, Majlis Perbandaran Kuala Kangsar (MPKK) at 2nd Floor Terminal Bus Kuala Kangsar, Perak Darul Ridzuan / Nor Liyana Rosland - Rosland, Nor Liyana (Faculty of Architecture, Planning and Surveying, 2011)
This project for this semester is about Proposed Interior Design of “Labu Sayong” Center at second floor Terminal Bus Kuala Kangsar Perak. This product “Labu Sayong” is so famous at Kuala Kangsar. The mission for this project is to create something new design for introduce this product “Labu Sayong” and attack people to come. The reason for this project is to create something new interior design, beside that it can also promote these products to local residents and tourists. The plan for this project is to proposed new interior design at second floor Terminal Bus Kuala Kangsar, Jalan Bendahara, 33000 Kuala Kangsar,Perak was choose after done survey and it seems that the site choose gives good impact and the surroundings suit the business purpose. The objective for this project is to create new center design with concept and style that can attract local residents and tourists to come.